The Effect of Social Media Influencer Characteristics on Purchase Intention on Beauty Products in Indonesia - Wirdatul Khomro Septian Candra (Fakultas Ekonomi, UIN Maliki Malang, 2023)
This study aims to determine the influence of content quality and attitude towards influencers on the purchase intention of beauty products, influenced by beauty influencer characteristics among Generation Z and Millennials in Indonesia. This research utilizes a quantitative method with a descriptive approach. The data will be analyzed using the CB-SEM method with IBM AMOS 24 software to process the 250 data obtained through a questionnaire. The findings reveal that content quality and attitude towards influencers mediate purchase intention. Variables such as perceived credibility, trustworthiness, expertise, likeability, and familiarity influence attitudes towards influencers for purchase intention in direct or indirect way. Additionally, trustworthiness indirectly affects purchase intention significantly through content quality. Simultaneously, similarity and parasocial interaction directly influence purchase intention. This study provides insights into the factors influencing consumer attitudes towards beauty influencers and content quality, positively impacting purchase intention. It is expected to assist entrepreneurs and marketers in understanding the contribution of beauty influencers on Instagram to purchase intention